Diabetes knowledge, medication adherence, and glycemic control among diabetic patients: A cross-sectional study in Jordan - Saba Madae&#;en, Eman Elayeh, Amal Akour, Tahanie AlQhaiwi, Bayan Shaggour, Rola Madain (Journal of Applied Pharmaceutical Science, 2020)
There is an increasing prevalence of diabetes and its associated complications worldwide and in Jordan. Enhancing the knowledge level of diabetes may help in glycemic control, but few studies in Jordan assessed that. Therefore, the objectives of the present study were to assess the level of diabetes knowledge among study participant and to study the potential predictors of glycemic control. The methodology involved conducting a cross-sectional quantitative study. Our study participants were patients treated in the Endocrine Clinic of Jordan University Hospital. As for the tools, we utilized Michigan Diabetes Knowledge test to assess the knowledge level of diabetes, Morisky Medication Adherence Scale for the assessment of medication adherence, and the level of HbA1c to indicate glycemic control. Study findings showed that the median score of knowledge was 13, (IQR, 4) (interquartile range) with a score range of 0–23. The median for medication adherence was 6 (IQR, 3) on a scale from 0 to 8 with zero being adherent. The data of the present study showed a moderate level of diabetes knowledge among study participants and low adherence scores to diabetes medications, with no correlations between variables of the study and the socio-demographic variables.
Keywords: Diabetes, glycemic control, medication adherence, diabetes knowledge.